Biodegradable hollowed mesoporous SeO2 nanoplatform loaded with indocyanine green for simultaneous NIR II fluorescence imaging and synergistic breast carcinoma therapy - Peng, Tingwei; Liu, Qing; Song, Hui; Zhang, Conghui; Wang, Xue; Ru, Ping; Xu, Tianzhao; Liu, Xinghui (Frontiers in Bioengineering and Biotechnology, 2023)
Contrast agents in the second window of the near-infrared region (NIR II, 1000–1700 nm) have several advantages and indocyanine green (ICG), which emits NIR II fluorescence, is clinically approved and its use has been widely investigated for in vivo imaging, specifically for delineating tumor outlines; however, insufficient tumor targeting and rapid physiological metabolism of free ICG has substantially impeded its further clinical application. Here, we constructed novel hollowed mesoporous selenium oxide nanocarriers for precise ICG delivery. After surface modification with the active tumor targeting amino acid motif, RGD (hmSeO2@ICG-RGD), the nanocarriers were preferentially targeted toward tumor cells and subsequently degraded for ICG and Se-based nanogranule release under tumor tissue extracellular pH conditions (pH 6.5). The released ICG acted as an NIR II contrast agent, highlighting tumor tissue, after intravenous administration of hmSeO2@ICG-RGD into mammary tumor-bearing mice. Importantly, the photothermal effect of ICG improved reactive oxygen species production from SeO2 nanogranules, inducing oxidative therapy. The synergistic therapeutic effects of hyperthermia and increased oxidative stress on 808 nm laser exposure induced significant tumor cell killing. Thus, our nanoplatform can generate a high-performance diagnostic and therapeutic nanoagent that facilitates in vivo tumor outline discrimination and tumor ablation.